Stress nation : escape the technology trap, eliminate stress, and reclaim rest - Hai, Justin (Wiley, 2025)
"In Stress Nation, serial entrepreneur Justin Hai exposes the invisible but devastating toll that modern technology has taken on our minds, bodies, and relationships. From sleepless nights to chronic anxiety and emotional disconnection, the symptoms are everywhere--and they're no accident. Blending hard science with sharp cultural commentary, Hai explains how our cortisol-driven stress response is being hijacked by screen addiction, digital overload, and algorithms engineered to keep us hooked. but this isn't just a wake-up call--it's a lifeline. Inside, you'll discover a clear, evidence-based roadmap to rebalance your hormones, improve your sleep, restore focus, and reconnect with yourself and others."--Page [4] of cover.